Multikulturalisme dalam Pendidikan Agama Islam dan Implementasinya pada Karyawan Toko Buku Gramedia - zahro, Zahro (Universitas Negeri Makassar, 2023)
Currently, the spirit of unity and integrity of the nation is being tested. Such as violent conflicts in the name of religion, radicalism to terrorism. The learning of Islamic religious education has an important role in instilling the values of multiculturalism to students which originate from the teachings of the Koran in order to create students who believe and fear God Almighty. Therefore, multicultural Islamic religious education needs to be realized as a medium in providing solutions to conflicts caused by differences in culture, religion, race, and other social conflicts. This study aims to describe and analyze the implementation of multicultural Islamic religious education in schools. This study uses a qualitative approach, which uses sources from journals, books, and internet sources. The results of this study can be used as an ideal example of implementing Islamic Religious Education learning based on multicultural values in schools.Keywords : Multiculturalism, Learning, Islamic Religious Education